Improvement of quality of life and symptoms after gastric electrical stimulation in children with functional dyspepsia. Issue 7 (25th February 2013) - Lu, P. L.; Teich, S.; Lorenzo, C. D.; Skaggs, B.; Alhajj, M.; Mousa, H. M.
Abstract: Background: Our objective is to evaluate the effect of gastric electrical stimulation (GES) on symptoms and quality of life for pediatric patients with functional dyspepsia (FD). Methods: Twenty‐four patients (16 female, median 15 years) were treated with GES for FD after a median of 24 months of symptoms (3 months–14 years). At baseline, 46% required tube feeds and 25% parenteral nutrition. Sixty percent had gastroparesis. The PedsQL GI Module (PedsQL) was completed for 18/24 both pre‐/post‐GES after a median of 8 months. Patients also completed the Symptom Monitor Worksheet (SMW) pre‐/post‐GES after a median of 6 months. Pre‐/post‐GES global health was also assessed. Key Results: Significant improvements were seen in multiple areas of the PedsQL, including stomach pain/upset, food/drink limits, heartburn/reflux, gas/bloating, patient worry, medication tolerance, and constipation ( P  < 0.05). A decrease was found in combined symptom severity/frequency based on SMW ( P  < 0.01). Improvements were made in all categories, including vomiting, nausea, early satiety, bloating, fullness, epigastric pain, and burning ( P  < 0.01). Improvements in PedsQL/SMW scores remained when analysis was limited to normal or delayed gastric emptying ( P  < 0.05, P  < 0.05). Thirteen percent needed tube feeds and 13% parenteral nutrition after GES. Sixty‐five percent reported that their health was much improved after GES vs 15% the same or worse. Five patients experienced complications, primarily mild abdominal discomfort. Conclusions & Inferences: In the largest series to date of pediatric patients who have undergone GES for FD, we found significant improvements in upper gastrointestinal symptoms, quality of life, and perception of global health. Patients were less dependent on tube feeding or parenteral nutrition.